Al 0.4Ga 0.6N/Al 0.15Ga 0.85N Separate Absorption and Multiplication Solar-Blind Avalanche Photodiodes With a One-Dimensional Photonic Crystal Filter - Kexiu Dong; Dunjun Chen; Biaobing Jin; Xishun Jiang; Jianping Shi (IEEE Photonics Journal)
An Al 0.15Ga 0.85N/Al 0.4Ga 0.6N separate absorption and multiplication avalanche photodiode (APD) integrated with the 1-D photonic crystal (PC) filter with a three-period antireflection coating between the air and periodic PC units on the back of the sapphire substrate are designed and studied. The calculated results show that the designed Al 0.15Ga 0.85N/Al 0.4Ga 0.6N APD has a much higher gain and a steeper spectral responsivity cutoff edge in the solar-blind region, and its peak responsivity and ultraviolet/visible rejection ratio are enhanced near 110% and 230%, respectively, when compared with the conventional AlGaN APD. Moreover, the antireflection coatings used in the designed APD can obviously improve the spectral response curve and the spectral responsivity due to its significant suppression to the reflectivity the in solar-blind region.